The Origins of the EPRDF and the Prospects for the Prosperity Party. (August 2021) - Lyons, Terrence
This paper presents the historical development of the authoritarian Ethiopian People's Revolutionary Democratic Front (EPRDF) with particular attention to its origins in civil war and its use of multi-national federal structures to balance centralizing dynamics and demands for regional autonomy. It argues that the reform process launched by Prime Minister Abiy and the formation of the successor Prosperity Party failed to overcome the challenges and political logics that undermined the EPRDF. The article concludes by examining the prospects of the center to manage these contradictions and bind together the distinct and highly polarized regions and political interests.